Agent-based modelling and simulation in the analysis of customer behaviour on B2C e-commerce sites. Issue 4 (1st November 2017) - Čavoški, Sava; Marković, Aleksandar
Abstract: This paper examines the development and application of agent-based modelling and simulation in the analysis of customer behaviour on B2C e-commerce websites as well as in the analysis of the effects of various business decisions regarding online sales. The methodology of the agent-based simulation used in this paper may significantly enhance the speed and quality of decision-making in electronic trade. The models developed for this research aim to improve the use of practical tools for the evaluation of the B2C online sales systems in that they allow for an investigation into the outcomes of varied strategies in the e-commerce site management as regards customer behaviour, website visits, scope of sales, income earned, etc. An agent-based simulation model developed for the needs of this research is able to track the interactions of key subjects in online sales: site visitors—prospective consumers, sellers with different business strategies, and suppliers.